Mother, A Symbol of Love And Affection: Peirce Semiotic Study In Lughat Al-‘Aalam Song Lyrics - Salamah, Nur; Sopian, Asep; Nurmala, Mia (Jurusan Pendidikan Bahasa Arab IAIN Ponorogo, 2024)
A song is a communication tool that combines musical instruments with language designed to elicit an emotional response from the soul, evoking moods such as joy, sadness, love, and anger. Foreign lyrics are often difficult to understand by listeners who do not understand the language, which hinders the understanding of the meaning and message conveyed by the author. The objective of this research is to conduct an analysis on the significance of Humood Alkhudher's Lughat Al-'Alam by employing Peirce's semiotic approach. Qualitative methods, specifically content analysis, will be utilized to examine the signs within the song's lyrics, employing Peirce's trichotomy as the analytical framework. The research findings indicate that the verses in these lyrics exemplify a comprehensive comprehension of the numerous privileges bestowed upon mothers in various facets of life, including their manifestation of tenderness, provision of safety, and bestowal of irreplaceable kindness. The use of language and symbols in the lyrics reflects the emotional relationship between a mother and child as well as the diversity of